Feminine Ideology, Body Appreciation, and Indirect Aggression in Girls - Buzgon, Julie; Crothers, Laura M.; Schreiber, James B.; Schmitt, Ara J.; Kolbert, Jered B.; Wadsworth, Jacob; Fidazzo, Angela; Barron, Mordechai; Steeves, Taylor (Frontiers in Education, 2022)
This study was an investigation of the possible relations and interactions between the feminine ideology, body appreciation, and indirect aggression within a sample of female children and adolescents. Participants included 45 female students (8 to 19 years of age) who completed measures assessing beliefs about and behaviors feminine ideology, body image (including body objectification), indirect bullying (including relational and social aggression), and social maturity. Analyses revealed that participants who rated themselves as having a weaker internalization of the objectification of one’s body (a subtype of feminine ideology) rated themselves as less likely to use socially-aggressive tactics than those with higher levels of body objectification. No other significant findings were noted. Implications for these findings and directions for future research are discussed.